Role of Digital Technologies in the Russian Economy - Gulmira NURGAZINA; Alexander ANISIMOV; Valentina BRITVINA; Galina KONYUKHOVA; Ekaterina BOBROVA; Olga PYATAEVA (Communications of International Proceedings, 2020)
The paper deals with the influence of "digital economy" development on production efficiency. The place of a country in the international arena and the welfare of its citizens depend on the ability of the state to implement an effective digitalization policy. In a market economy they help to increase the competitiveness of business entities, increase the income of the population and solvent demand for goods and services, expand international economic ties and attract foreign capital, increase the efficiency of production as a whole. Digital technologies are a factor in the growth of innovations that contribute to the creation and application of digital technologies, a digital platform, in today's Russian economy.
Keywords: Digitalization; Production Efficiency; Innovativeness; Competitive Advantages; Innovations.